2019
DOI: 10.1002/ejlt.201800295
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Technology Parameters: Effects on Phenolics in Olive Paste and Oil in Relation to Enzymatic Activity

Abstract: In this paper, the occurrence of secoiridoid aglycones via degradation of phenolic glucosides which have strong effects on commercial, nutritional, and sensory properties of olive oil is studied. The experiment consists in the sonication treatment of Chemlali and Memecik cvs. olive paste three times for 4, 8, and 10 min. This kind of approach has never been used in determining the partition and degradation of phenolics during extraction. Concerning phenolic content present in Chemlali olive oil extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Among them, the US technology seems to be a promising application in the field of VOOs industry, due to its mechanical and thermal effects when applied on olive paste [12] , [13] , [14] , [15] , [19] , [20] , [34] . Besides, according to several studies, the olive oils obtained from treated olive paste with US in the malaxation step did not present changes in the quality indices, fatty acid composition and volatile aromatic compounds of the VOO, however controversial results on phenols content have been reported by different authors [12] , [14] , [20] , [21] , [23] , [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the US technology seems to be a promising application in the field of VOOs industry, due to its mechanical and thermal effects when applied on olive paste [12] , [13] , [14] , [15] , [19] , [20] , [34] . Besides, according to several studies, the olive oils obtained from treated olive paste with US in the malaxation step did not present changes in the quality indices, fatty acid composition and volatile aromatic compounds of the VOO, however controversial results on phenols content have been reported by different authors [12] , [14] , [20] , [21] , [23] , [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in a subsequent study by the same laboratory, a significant increase in polyphenols was observed in the sonicated oils, which was attributed to the effect of US on polyphenol oxidase activity [ 30 ]. In a recent research on the effects of US on the phenolic content of oil, the concentration of secoiridoids increased by 60% when using depitted olives, and this positive effect was enhanced when applying longer US treatment [ 32 ].…”
Section: Influence Of Emerging Technologies On Evoo Production (Yimentioning
confidence: 99%
“…In recent years, numerous alternative techniques to overcome these problems have been developed. Among them, there are emerging microwaves, supercritical fluids, ultrasound or the addition of a co-adjuvant, [1][2][3][4][5] as well as pulsed electric field, [6][7][8] Therefore, ultrasound and microwave have many applications not only in our homes but also in industry. In order to increase the oxidative stability capacities of virgin olive oil (VOO), by reducing the extraction time and increasing the olive oil quality, many researchers teams proposed many studies to improve olive oil performance.…”
Section: Introduction *mentioning
confidence: 99%
“…Therefore, Malheiro et al 10 studied the influence of introducing microwaves and ultrasounds on the extraction of olive oil in point of view: oil yields and quality. For example, Yahyaoui et al 4 studied the phenolic compounds present in Chemlali and Memlick olive pastes and oils obtained after ultrasound treatment of depitted olive paste and whole olive samples 4 . They found that the first one were the most affected.…”
Section: Introduction *mentioning
confidence: 99%